Women, Aging, Health and Quality of Life: A framework for action and policy formulations - G. Padmaja; Rekha Pande; Pavneet Kaur (ACHSM, 2023)
The population of the elderly in the world will double from 2015 to 2050, reaching nearly 2.1 billion. The ageing population suffers from physical, mental health, and psychological well-being. There such customized policy that caters to helping the ageing population. The current examination studies ageing women, their health, and their quality of life () in India. The study tried to capture the two major and vast diversified areas. Respondents were randomly selected from four south and north Indian states. The present investigation covered 64 cities in these four states and collected 1,100 samples. The data analysis revealed that QoL has a significant difference with different demographic factors as well as health status, Literacy level, marital status, socioeconomic status, and health status of elderly women. Most of them suffer from diabetes, hypertension, and digestive system issues, so they need regular medical care and attention. Further data analysis unearthed that most ageing women belong to middle and lower socio-economic backgrounds. The government should focus more on their financial assistance and food security and arrange proper counselling therapy for their mental health to improve their QoL. The study contributes to the constructive and reflective handling of the health and well-being of the ageing female population. Policymakers must look into the health issues of the elderly population and make customised policies and actions that can assist the elderly population.